Literacy and the language awareness hypothesis. Issue 2 (3rd July 2019) - Francis, Norbert
ABSTRACT: In the study of reading and writing, the concept of language awareness has come forward for increased attention: that awareness of language form and pattern may be a central contributing factor that explains learning beyond basic beginning level attainment. Cross-cultural and cross-language evidence from different disciplines is important to take into account for a better understanding of the cognitive processes that explain the language awareness factor. Examples from the multilingual Western Hemisphere, from the contact between the American and European languages, are especially relevant because of the time scale of available data (over 2000 years for the first full writing system, successfully deciphered) and the closeness of contact and extensive interaction between the languages (over 500 years). Among the most prominent and thoroughly studied are findings from historical and anthropological research on literacy in the Mayan and Nahuatl languages, the latter from the early Spanish colonial era, the former from the pre-classical period of Mayan civilisation. The findings from this work inform studies of literacy learning among all modern day indigenous language bilingual learners in both Latin America and North America. As an illustration, results from a bilingual (Nahuatl-Spanish) literacy learning project in Puebla state, Mexico, are summarised.